The Impact of Work-Life Balance on Employee Performance: An Evaluative Study of Health and Safety Industry in Nigeria - Ihwughwavwe, Sadat Itohan; Shewakramani, Rekha (International Journal of Humanity and Social Sciences, 2024)
Purpose: The purpose of this research is to explore the impacts of work-life balance on the performance of employees in the Nigerian health and safety industry using interviews and quantitative based online questionnaire involving one hundred participants from ten different companies. Methodology: Eighty three fully completed and returned questionnaires were utilized for the purpose of the research. The questionnaire encompasses the demographic survey of participants, well-being, job satisfaction and job performance-oriented questions. Statistical Package for Social Sciences (SPSS) was used in developing a linear statistical relationship between employee performance and productivity as the dependent variable and employment factors - extent of work-life balance and impact of work-life balance as the independent variables respectively. Findings: 2.6295, 3.1325 and 2.8554 mean values were recorded for data generated from Work-Life Balance; Company Policies and Performance and Company Support Policy on Work-Life Balance respectively. Based on the mean values obtained, normality of the variables under study is statistically attainable. Findings from the study depict positive relationship for the variables under study. It also implies less stress in the work environments under study. Similarly, findings in terms of work environment, team support, area of specialization, workload, flexibility, supervisors' commitment to employee's personal lives, work force and discipline have indicated that the teaming population of health and safety employees have, to a reasonable degree, a control over their time and personal lives. Additionally, the company's support and policies for work-life balance are said to be reasonable enough as they pave ways for sound employees' performance. Unique contribution to theory, practice and policy: companies should improve on support and policies/programs that have direct impact on work-life balance - telecommuting, compression of work week; strict adherence to the work hours stipulated by law and any extra hour(s) spent by an employee should be adequately compensated; develop and implement a business continuity plan and carry out manpower audits to determine areas of under manning with a view of providing the qualified manpower to man the company operations. These will pave ways for the employees to develop themselves educationally, create time for families and friends, thereby, aiding the concept of meaningful work-life balance.